High Intensity Swimming Exercise Decline Memory Retention of Young White Rats (Rattus norvegicus) - Argarini, Raden; Harjanto, J. M.; Effendi, Choesnan; Herawati, Lilik; Irwadi, Irfiansyah (ANIMA Indonesian Psychological Journal, 2012)
The aim of this study was to test whether high intensity swimming exercise on young white mice affect memory retention. A Randomized Post-Test Only Control Group Design was used. Subjects were 20 male rats (Rattus norvegicus wistar strain), age 1 to 1.5 months, body weight 60-100 grams, which were divided randomly into 2 groups (each consist 10 rats). The treatment group got the high intensity swimming exercise (plus 9% of body weight added load). Each treatment was conducted once a day during 1 minute and 45 seconds, three sets with rest period three times the exercise time, for four weeks. Memory retention was measured through a Y- maze test in two sessions, each with six replications. Results showed that memory retention between groups on day 4, was (65.00 ± 31.38)% in the control group, and (30.56 ± 26.68)% in the treatment group. Independent t-test results revealed significant differences between the control group and the treated group (p = .020). The conclusion is that high intensity exercise decline memory retention in young white rats. Tujuan penelitian ini adalah menguji apakah latihan renang intensitas berat pada tikus putih muda memengaruhi retensi memorinya. Desain penelitian adalah Randomized Post-Test Only Control Grup. Subjek adalah 20 ekor tikus putih (Rattus norvegicus strain wistar) jantan, umur 1-1,5 bulan, berat badan 60 – 100 gram. Melalui random assignment subjek dibagi menjadi kelompok kontrol dan kelompok perlakuan (masing-masing 10 ekor) Kelompok perlakuan (10 ekor) diberi latihan renang dengan intensitas berat (beban 9% berat badan). Perlakuan diberikan satu kali per hari selama 1 menit 45 detik, tiga set dengan waktu istirahat tiga kali lama waktu latihan, selama empat minggu. Retensi memori diukur melalui test Y-maze selama dua sesi, masing-masing enam kali pengulangan. Hasil setelah hari ke-empat, pada kelompok kontrol didapatkan rerata (65.00 ± 31.38)%, kelompok perlakuan (intensitas tinggi) adalah (30.56 ± 26.68)%. Hasil independent t test menunjukkan perbedaan yang bermakna antara kelompok kontrol dan perlakuan (p = .020). Simpulan penelitian ini adalah latihan renang dengan intensitas tinggi menurunkan retensi memori pada tikus putih muda.